The Influence Of Product Quality And Price On Purchasing Decisions On Mother Of Pearl Products From Tasya Farasya (Case Study of Students Management of Indonesian Islamic University) - Anetta Marriel Santoso; Agus Abdurrahman (Cita konsultindo, 2024)
This study aims to investigate the influence of product quality and price on purchase decisions for the